Strategic Analysis for a Coffee Company– Part 1 (British Journal of Multidisciplinary and Advanced Studies, 2025)
The purpose of this paper was to conduct a strategic analysis of a Coffee Company in Durban, South Africa. Environmental analysis tools were used such as PESTLE for a macro analysis and Porters Five Forces for a micro analysis in order to identify the factors that can impact the performance of this company. Porter’s value chain and SWOT analysis was used to devise a successful strategy for the future of the company. The significant findings revealed that the Coffee Company must focus on market expansion, franchising strategy and acquisition. A strategic plan to address these opportunities will be presented in a future paper.